Observation of dynamic maximum in a turbulent cascade on the surface of liquid hydrogen - Remizov, I.A.; Brazhnikov, M.Yu.; Levchenko, A.A. (Физика низких температур, 2016)
We report on the experimental observation of energy accumulation near the high frequency boundary of the inertial range in the spectrum of turbulence in a system of capillary waves on the surface of liquid hydrogen driven by a harmonic force. The effect is manifested as a local maximum in the spectrum of pair correlation function of the surface elevation. This phenomenon is dynamical and can be seen only during reconfiguration of the turbulent cascade caused by waves generation of below the driving frequency.